A rare case of sacroccocygeal teratoma type II with malignant yolk sac component (Indian Journal of Child Health, 2024)
Sacrococcygeal teratoma (SCT) is one of the most common neoplasms diagnosed prenatally. Obstetric ultrasound plays a role in the diagnosis and management of these tumors during pregnancy. In this case report, we discuss the postnatal outcome and a multidisciplinary approach in a neonate with massive SCT and preterm delivery. A 36-year-old mother with a pregnancy complicated by gestational diabetes and polyhydramnios and a large mass in the sacrococcygeal region delivered a girl child at 35+4 weeks gestation by elective cesarean section following an in utero transport to our center. The teratoma, measuring 15×12 cm, was completely excised along with the coccyx and perineum postnatally on day 3 of life. As histopathology revealed a small cluster of pre-malignant yolk sac tissue, the infant is under the care of a hemato-oncologist. Multidisciplinary care including good obstetric practices with serial monitoring with ultrasonography, in utero transfer to a center with Level III Neonatal Intensive Care, and pediatric surgery services with good nursing care result in improved outcomes in these complexes prenatally diagnosed tumors.